Optimizing quality of life for prostate cancer patients: a comprehensive approach - Rangga Juliar Adista; Jufriady Ismy (Green Publisher Indonesia, 2025)
This comprehensive review examines evidence-based interventions for optimizing quality of life in prostate cancer patients. Synthesizing a multifaceted approach, the review encompasses lifestyle modifications, educational support, cognitive-behavioural therapies, and survivorship care coordination. Robust evidence underscores the efficacy of integrating tailored exercise regimens, dietary modifications, and multidisciplinary care teams to address the multifaceted physical and psychological impacts of prostate cancer. Cognitive-behavioural approaches demonstrate significant value in mitigating emotional distress, while survivorship care coordination, interfacing with primary care, emerges as crucial for ensuring seamless transitions and long-term health optimization. Acknowledging inherent limitations, the review delineates key research recommendations to inform future investigations, emphasizing the dynamic nature of healthcare advancements in the ongoing pursuit of superior patient outcomes.